Impact of service changes on neonatal transfer patterns over 10 years. Issue 3 (9th November 2006) - Cusack, Jonathan M; Field, David J; Manktelow, Bradley N
Abstract : Introduction: Many changes have been made to the staffing and organisation of neonatal care in the UK in the past 10 years. This study assessed the extent to which these changes had affected the transfer of babies between different parts of the service. Methods: Data from the Trent Neonatal Survey, an ongoing study of neonatal intensive care activity in the former Trent Health Region of the UK, were used to evaluate neonatal inter-hospital transfers over a 10-year period, from 1 January 1995 to 31 December 2004. The number of transfers and the types of transfer were analysed and trends in gestation and disease severity over the study period were assessed. Rates of "inappropriate transfer" were also identified. Results: 8105 babies were transferred over the period; 2294 babies underwent urgent postnatal transfer and this equates to approximately two such transfers every three days. The maximum number of journeys by any one baby was eight. Intensive care activity rose during the 10 years but the number of inappropriate transfers remained persistently high. Conclusions: Organisational changes in neonatal care during the 10-year period have been insufficient to deal with the rising demand, as reflected by the persistently high rate of inappropriate transfers.